Revisión de los sistemas de control de versiones utilizados en el desarrollo de software - Tello Leal, Edgar (Editorial bonaventuriana, 2018)
Nowadays, one of the main challenges faced by software developers is creating efficient and quality products without impairing time or costs. This goal only can be achieved if people involved in the process can have all the information related to the project. Version control systems are applications that contribute in the software development process; they make easier the management of version control of source code files produced by developers, they also provide tools for the fusion and generation of a new project version thus allowing that different developers could work on the same project without causing data loss or blocking the access to files. Additionally, version control systems allow retrieving previously generated files, which can be used to fix system errors. In this work we present a review of the main software applications available for version control management from the point of view of their use in software development. Control version systems are also analyzed according to the management method of the information stored in repositories, by describing the process of creating, updating, and generating a new version of source code files stored in there.